Is ethnicity a risk factor for severe retinopathy of prematurity?. Issue 3 (29th November 2009) - Aralikatti, Anil KV; Mitra, Arijit; Denniston, Alastair K O; Haque, M Sayeed; Ewer, Andrew K; Butler, Lucilla
Abstract : Objective: To assess the risk of severe retinopathy of prematurity (ROP) requiring treatment in different ethnic groups. Design: Retrospective observational study on ROP screening and treatment. It involved a cross-sectional review of all eligible infants over a seven-year period. Statistical tests used were the Kruskal-Wallis test and Mann-Whitney U test. Logistic regression was used to control for any differences in birth weight and gestational age. Setting: City Hospital and Birmingham Women's Hospital, Birmingham, UK. Results: 1690 preterm infants underwent ROP screening. Birth weight was lower in black (1142.5 g) and Asian infants (1180 g) when compared to white infants (1196.5 g). Gestational age was lower in black infants (28.5 weeks) compared to Asian and white infants (both 29 weeks). Compared to white infants, the odds of severe ROP requiring treatment was higher in Asian infants (odds ratio (OR): 2.52; 95% CI 1.41 to 4.50) and black infants (OR: 2.51; 95% CI 1.30 to 4.86). The additional risk from ethnicity was present even after adjusting for birth weight and gestational age (adjusted OR for Asian vs white infants: 2.45; 95% CI 1.334 to 4.497); (adjusted OR for black vs white infants: 2.0; 95% CI 1.004 to 4.014). Conclusions: Ethnicity is a risk factor for severe ROP. Asian and black infants have a higher risk of developing threshold ROP compared to white infants.